Arbesův život a jeho romaneta z pohledu literárního vědce - Kolářová, Ivana (Stylistyka, 2002)
There is written about some interesting and important life stories of the Czech author of many tales of mystery and imagination Jakub Arbes in the Novel by František Všetièka PPed branami Omegy. F. Všetiëka depicts the episodes ofArbes’s life in connection with subjects-matters of the tales of mystery and imagination: there are some events of Arbes "s Life (the events in the year 1848, imprisonment, the school years), that are described in the "tales", too, There were some famous persons, who "has been changed" into literary characters (Arbes’s favour teacher of catechism F. Schneider, the count Buquoy, the keeper in the prison in the town Ceská Lípa; some persons are entitled by the Greek letters Alfa, Beta, Gamma, Delta, Epsilon, Zeta, Eta). Some events, places and some persons are depicted in VšetiCka’s novel by language expressions similar to the expressions, that used Jakub Arbes in his tales of mystery and imagination (for example by expressive adjec tives škaredå, nevlídný, šílený, tgjtrlík). Some scenery of the novel Pied branami Omeo are depicted in the tales of mystery and imagination, too (in the prison, in the front of the Buquoy"s palace in Prague in 1848). F. Všetiëka is well-known Czech literary theorist dealing almost with the structure and composition of the literary texts. He used in the novel Pied branami Omeo methods of text compositions, the way Jakub Arbes has used them in his tales of mystery and imaginations, too (for example combination the chronology and retrospective, of the real events and imagination).